The Permissible under Heating Conditions Torque of a Frequency-Controlled Synchronous Motor of Permanent Magnets - B. I. Firago; S. V. Aleksandrovsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The variable speed electrical drives for industrial mechanisms with a constant static torque usually operate in a large range of speeds and loads. Along with this, for any speed of a given range the electrical drive motor is to provide a continuous permissible torque without overheating. Mostly the electrical motors have self-ventilation; the ventilator being located on the motor shaft. In such motors heat dissipation depends on a motor speed. The permissible continuous motor torque is determined out of a heat balance equation where power losses being converted into heat must be transferred in the ambient space and the motor temperature must not be over a permitted level for a given class of winding insulation under the certain ambient temperature. A heat balance equation is usually obtained on a basis of a one-mass motor heat model, i. e. the model that was used in this research. But even the one-mass heat model gives a non-linear heat balance equation. In order to get convenient analytical expressions out of the motor heat balance equation, it is necessary to take some justified assumptions; the latter was also implemented in this research. As a result, formulas have been obtained by which the long-term permissible motor torque can be calculated as a function of the relative speed of the rotor at a given ambient temperature. For the examples presented in the articles we chose (20 and 40 °С as a standard temperature for the thermal calculation of electrical machines). Dependences of a relative permissible continuous motor torque m on a relative frequency value (or relative rotor speed) are presented for three synchronous motors with permanent magnets and rated power of 3; 25 and 250 kW.